Regioselective ring expansion followed by H-shift of 3-ylidene oxindoles: a convenient synthesis of N-substituted/un-substituted pyrrolo[2, 3-c] quinolines and marinoquinolines. Issue 60 (30th October 2019) - Ramu, Gopathi; Ambala, Srinivas; Nanubolu, Jagadeesh Babu; Nagendra Babu, Bathini
Abstract : Herein, we report a simple and metal-free protocol for the synthesis of 4-oxo-4, 5-dihydro-3 H -pyrrolo[2, 3- c ]quinolines. Abstract : Herein, we report a simple and metal-free protocol for the synthesis of 4-oxo-4, 5-dihydro-3 H -pyrrolo[2, 3- c ]quinolines. The present method under mild reaction conditions with wide functional group compatibility gives several unexplored N-substituted/unsubstituted 4-oxo-4, 5-dihydro-3 H -pyrrolo[2, 3- c ]quinolines and marinoquinolines in good to excellent yields. Mechanistic insights for the synthesis of N-substituted pyrroloquinolines reveal the ring expansion of 3-ylideneoxindoles and H-shift as the key steps.